A Survey: Analytics of Web Log File Using Map Reduce and Hadoop - Pateriya, Rahul; Mishra, Nishchol; Sharma, Sanjeev (International Journal of Computer Sciences and Engineering, 2025)
The web is vast, diverse and dynamic and increases scalability, temporal data and multimedia issues respectively. The expansion of the Internet has given rise to a wealth of data as big data that is now available for user access. Different types of data must be managed and organized so that can be accessed by different users effectively and efficiently. The log analysis is an important issue for the web application. Log file is not to be over emphasized as a source of information in systems and network management. Whereas conduct efficient investigation and gathering of use full information need to correlate different log file. Task of analyzing event log files with the ever-increasing size and complexity of today’s event logs has become cumbrous to carry out manually. Nowadays latest spotlighted is automatic analysis of these logs files. This paper is a review of the basics of log analysis as big data in the web environment.